Phosphine-free Stille-Migita chemistry for the mild and orthogonal modification of DNA and RNA - Krause, André; Muttach, Fabian; Jäschke, Andres (Chemistry - a European journal, 2014)
An optimized catalyst system of [Pd2(dba)3] and AsPh3 efficiently catalyzes the Stille reaction between a diverse set of functionalized stannanes and halogenated mono-, di- and oligonucleotides. The methodology allows for the facile conjugation of short and long nucleic acid molecules with moieties that are not compatible with conventional chemical or enzymatic synthesis, among them acid-, base-, or fluoride-labile protecting groups, fluorogenic and synthetically challenging moieties with good to near-quantitative yields. Notably, even azides can be directly introduced into oligonucleotides and (deoxy)nucleoside triphosphates, thereby giving direct access to “clickable” nucleic acids.
Gesehen am 23.10.2020